Political Expressionism of Women Politicians Amidst the Discourse of the Patriarchal Paradox - Yeby Ma'asan Mayrudin; M. Dian Hikmawan; Moh. Rizky Godjali; Herlina (Politicon : Jurnal Ilmu Politik, 2026)
The barriers in expressing political missions for women politicians are due to the dominance of patriarchal structures. This article aims to discuss the dialectic of political expressionism of Banten women politicians amidst the paradox of patriarchy in the organization of political parties and their existence in parliament. Political expressionism is a perspective that attempts to describe the expression of political attitudes and ideas that tend to be emotional and reflective. Therefore, the political expressionism of women politicians is an expression of sentimental political attitudes and ideas of women politicians due to the mental pressure of double burdens, gender discrimination and symbolic violence. A qualitative approach with a transcendental phenomenological is used to explain the "common meaning of their lived experience" of 12 women politicians (Party chairpersons, members of the provincial and district/city DPRD, and legislative candidates who failed to be elected). We use coding analysis of Creswell’s phenomenology specifically epoche, significant statement, meaning unit, textural and structural description.  The findings of this research are: First, women politicians are able to provide new meanings and values in political dynamics based on the manifestation of their political expressionism. The focus of the political expression of women politicians in Banten are four forms, namely resistence, conformity, existence, dan subservience; Second, the models of patriarchal paradox that makes women subordination, violence and double burdens (face the dilemma of dual identity in the public and domestic spheres), are successfully negotiated by the struggle of women politicians through authentic communication and expression strategies that increase the legitimacy of the role of women politicians. This research contributes to the development of political science through the combination with the discipline of art "expressionism" and a gender perspective in dissecting the power relations between the existence of women politicians and the discourse of the patriarchal paradox.